Pemberdayaan Ekonomi Masyarakat Melalui Pelestarian Makanan Tradisional “Krupuk Kluntung” Di Desa Singojuruh Kabupaten Banyuwangi - Nurul Inayah; Abdi Fauji Hadiono; Lely Ana Ferawati Ekaningsih; Siti Aimah (IAI Darussalam, 2018)
Singojuruh Village is one of the villages whose population is relatively dense compared to other villagers in Singojuruh Subdistrict. Most Singojuruh residents prefer to work outside the area as laborers or as farm laborers in their own villages, this is due to the lack of employment opportunities in the village. Whereas the mothers in the village preferred the work of the labors to make montes taken from one of the monte craftsmen. Kluntung crackers themselves are one of the traditional foods from Singojuruh Village, especially Pasinan Hamlet, because these crackers have long existed, inheritance from previous ancestors but unfortunately these crackers are almost extinct because the printing process is so difficult that not many people can print and painstakingly in making these crackers. So by empowering the community with the making of kluntung crackers, it is hoped that it will be able to increase people's income while preserving traditional food from an endangered ancestral heritage. Key Words: Empowerment, kluntung crackers, traditional food, economic improvement